2022
DOI: 10.1021/acs.joc.2c00614
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of 2-Methylnicotinonitrile through Degenerate Ring Transformation of Pyridinium Salts

Abstract: Nucleophilic recyclization of pyridinium salts involving a CCN interchange ring transformation for the synthesis of 2-methylnicotinonitrile derivatives was herein developed. 3-Aminocrotononitrile (3-ACN) produced in situ from CH3CN acted as a C-nucleophile, as well as the source of CH3 and CN groups, which was supported by isotope-labeling and control experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Subsequently, Trofimov reported the cyclization of available acylethynylpyrroles with acetonitrile to provide a series of pyrrolyl-pyridines in 63-87% yields [60]. In 2022, Duan et al reported a new strategy for the synthesis of 2-methylnicotinonitriles 74 through the degenerate ring transformation of N-substituted pyridinium salts 73 (Scheme 18) [61]. The reaction was carried out using potassium hexamethyldisilazide (KHMDS), benzoic acid (BA), and benzyl triethyl ammonium chloride (TEBA) as additives in acetonitrile at 90 • C for 20 h. This reaction is applicable to various phenyl-substituted 4-phenyl-1-vinylpyridin-1-ium tetrafluoroborates and 3-aryl pyridinium salts, while 4-alkyl-substituted pyridinium salts are limited.…”
Section: Synthesis Of 3-cyanopyridinementioning
confidence: 99%
“…Subsequently, Trofimov reported the cyclization of available acylethynylpyrroles with acetonitrile to provide a series of pyrrolyl-pyridines in 63-87% yields [60]. In 2022, Duan et al reported a new strategy for the synthesis of 2-methylnicotinonitriles 74 through the degenerate ring transformation of N-substituted pyridinium salts 73 (Scheme 18) [61]. The reaction was carried out using potassium hexamethyldisilazide (KHMDS), benzoic acid (BA), and benzyl triethyl ammonium chloride (TEBA) as additives in acetonitrile at 90 • C for 20 h. This reaction is applicable to various phenyl-substituted 4-phenyl-1-vinylpyridin-1-ium tetrafluoroborates and 3-aryl pyridinium salts, while 4-alkyl-substituted pyridinium salts are limited.…”
Section: Synthesis Of 3-cyanopyridinementioning
confidence: 99%